Modernization Of The Educational Process Based On Digital Technologies - Uktamova, Moxigul; Omonjonova, Maftuna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the issue of modernization of the educational process based on digital technologies. Digital platforms, online educational tools and innovative pedagogical technologies are gaining importance in the modern education system. The article scientifically covers the theoretical foundations of digital education, its classification and application in the higher education system. Also, the effectiveness, pedagogical capabilities and development prospects of digital education are analyzed based on the research of world and local scientists. The results of the research are important in improving the quality of education, modernizing the educational process and forming a modern pedagogical environment.